2021
DOI: 10.32526/ennrj/19/2021008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fluorescent Dissolved Organic Matter in an Affected Pollution Raw Water Source using an Excitation-Emission Matrix and PARAFAC

Abstract: Cikapundung River is the main raw water source for 2-millions inhabitants of Bandung city but has been severely deteriorated due to organic pollution such as cattle manure, domestic, and agriculture wastes. Dissolved Organic Matter (DOM) in raw water can influence the process of water treatment. This study characterized and identified the origins of fluorescent DOM (FDOM) in Cikapundung River. Raw water samples were collected from intake outlets during dry and rainy seasons and analyzed using Fluorescence Exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
1
4
0
1
Order By: Relevance
“…Another previous study has found that BIX>1 could also be an indication that the tryptophan-like compound was more predominant than the humic-like compound (Gabor et al, 2014). Moreover, the results of the FI and BIX values have confirmed the organic pollution in the settlementimpacted watershed (Cimahi River), similar to those found in a main urban river in Bandung City (Cikapundung River) during the dry season when the water quality worsened (FI=1.55-3.23; BIX=0.62-1.33) (Sururi et al, 2021). FDOM in watersheds impacted by anthropogenic activities typically has lower molecular weight with hydrophobic and aromatic characteristics (Zhao et al, 2009;Zhao et al, 2006).…”
Section: Fdom Parameters and Compoundssupporting
confidence: 62%
See 3 more Smart Citations
“…Another previous study has found that BIX>1 could also be an indication that the tryptophan-like compound was more predominant than the humic-like compound (Gabor et al, 2014). Moreover, the results of the FI and BIX values have confirmed the organic pollution in the settlementimpacted watershed (Cimahi River), similar to those found in a main urban river in Bandung City (Cikapundung River) during the dry season when the water quality worsened (FI=1.55-3.23; BIX=0.62-1.33) (Sururi et al, 2021). FDOM in watersheds impacted by anthropogenic activities typically has lower molecular weight with hydrophobic and aromatic characteristics (Zhao et al, 2009;Zhao et al, 2006).…”
Section: Fdom Parameters and Compoundssupporting
confidence: 62%
“…However, other studies have reported that the local urban land uses are related to considerable changes in the inputs of the terrestrial humic-like compounds in the Zhujiang River (Meng et al, 2013) and Lake Tianmu (Shi et al, 2020). Sururi et al (2021) have reported pollution in the Cikapundung River, the main raw water source for Bandung City, Indonesia, by direct discharges of cattle manure, domestic and agricultural wastes, leading to an increment of proteinlike DOM such as tryptophan in this urban river. Raw water with an abundant tryptophan-like compound enhances microbial metabolism stimulation, hence adding difficulties for conventional water treatment (WTP) which is mostly implemented in Indonesia and other developing countries to maximumly remove DOM (Sururi et al, 2020).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Limbah domestik berupa senyawa organik yang dibuang oleh pemukiman diduga kuat menyebabkan tingginya konsentrasi COD (Sururi et al 2021). Menurut Lee and Nikraz (2015), kuantitas oksigen yang diperlukan dalam pengoksidasian semua senyawa organik yang hadir secara biologis dan inert menjadi karbon dioksida dan air disebut dengan COD.…”
Section: )unclassified